CeVO4/rGO nanocomposite: facile hydrothermal synthesis, characterization, and electrochemical hydrogen storage - Rezayeenik, Mahsa; Mousavi-Kamazani, Mehdi; Zinatloo-Ajabshir, Sahar (Applied physics. A, Materials science & processing, 2023)
In this paper, with the aim of improving hydrogen storage efficiency, cerium vanadate/reduced graphene oxide (CeVO 4 /rGO) nanocomposite was synthesized through a one-step hydrothermal method due to its unique characteristics, including suitable electrochemical behavior, high specific surface area, and high porosity. In addition to controlling the growth of CeVO 4 nanoparticles, hydrazine reduces graphene oxide (GO) to reduced graphene oxide (rGO) and enables one-step synthesis. FESEM images showed that the rod-like CeVO 4 nanoparticles were dispersed on the graphene plates. According to the obtained storage results, with the addition of graphene, the synergistic effect between the layers has increased and, as a result, the hydrogen storage capacity has increased. The highest amount of electrochemical storage of hydrogen in the synthesized nanocomposite was about 5430 mAh/g, which is a significant result compared to other nanostructures used.